Developing a scale for assessing coping behavior in situations of danger - N. V. Rodina; O. Iu. Dotsenko; A. V. Kernas; L. P. Pereviazko; L. K. Vornikova (Journal of Ophthalmology, 2022)
Background: The paper is focused on developing a psychodiagnostic tool for assessing coping behavior in situations of danger. Studies of coping behavior became increasingly important with the beginning of the Russian invasion in Ukraine on February 24, 2022. The version developed may become a reliable auxiliary tool for assessing the adaptive capacity of the personality, which is believed to be promising and of increasing importance for further studies.